Targeting MYC activity in double-hit lymphoma with MYC and BCL2 and/or BCL6 rearrangements with epigenetic bromodomain inhibitors - Li, Weiping (J Hematol Oncol, 2019)
Double/triple-hit lymphomas (DHL/THL) account for 5–10% of diffuse large B cell lymphoma (DLBCL) with rearrangement of MYC and BCL2 and/or BCL6 resulting in MYC overexpression. Despite the poor prognosis of DHL, R-CHOP chemotherapy remains the treatment backbone and new targeted therapy is needed. We performed comprehensive cytogenetic studies/fluorescence in situ hybridization on DLBCL and Burkitt lymphoma cell lines (n = 11) to identify the DHL/THL DLBCL in vitro model. We identified MYC/IG in Raji and Ramos (single hit); MYC/IG-BCL2 (DHL) in DOHH2, OCI-LY1, SUDHL2, and OCI-LY10; MYC/IG-BCL2/BCL6 (THL) in VAL; and no MYC rearrangement in U2932 and HBL1 (WT-MYC). Targeting MYC in the DHL/THL DLBCLs through bromodomain extra-terminal inhibitors (BETi) (JQ1, I-BET, and OTX015) significantly (p < 0.05) reduced proliferation, similar to WT-MYC cells, accompanied by decreased MYC but not BCL2 protein. Moreover, BETi suppressed MYC transcription and decreased BRD4 binding to MYC promoter in DHL cells. CD47 and PD-L1 are immunoregulatory molecules often expressed on tumors and regulated by MYC. High levels of surface CD47 but not surface PD-L1 was observed in DHL/THL, which was reduced by JQ1 treatment. BETi in combination with Pan-HDAC inhibitor had a limited effect on survival of DHL/THL, while combination of BETi and BCL2 inhibitor (ABT-199) had a significant (p < 0.005) inhibitory effect on survival followed by BCL-XL inhibition. Overall, the data suggests that MYC-expressing DLBCLs are probably addicted to the MYC-oncogenic effect regardless of MYC rearrangements. In summary, we identified an in vitro model for DHL/THL DLBCLs and provide evidence for the therapeutic potential of BET inhibitor alone or in combination with BCL2 inhibitor. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13045-019-0761-2) contains supplementary material, which is available to authorized users.